The Ice‐Free Topography of Svalbard. Issue 21 (5th November 2018) - Fürst, Johannes J.; Navarro, Francisco; Gillet‐Chaulet, Fabien; Huss, Matthias; Moholdt, Geir; Fettweis, Xavier; Lang, Charlotte; Seehaus, Thorsten; Ai, Songtao; Benham, Toby J.; Benn, Douglas I.; Björnsson, Helgi; et al.
Abstract: We present a first version of the Svalbard ice‐free topography (SVIFT1.0) using a mass conserving approach for mapping glacier ice thickness. SVIFT1.0 is informed by more than 1 million point measurements, totalling more than 8, 700 km of thickness profiles. SVIFT1.0 is publicly available and represents the geometric state around the year 2010. Our estimate for the total ice volume is 6, 199 km 3, equivalent to 1.5‐cm sea level rise. The thickness map suggests that 13% of the glacierized area is grounded below sea level. A complementary map of error estimates comprises uncertainties in the thickness surveys as well as in other input variables. Aggregated error estimates are used to define a likely ice‐volume range of 5, 200–7, 300 km 3 . The ice front thickness of marine‐terminating glaciers is a key quantity for ice loss attribution because it controls the potential ice discharge by iceberg calving into the ocean. We find a mean ice front thickness of 135 m for the archipelago (likely range 123–158 m). Plain Language Summary: Svalbard is an archipelago in the Arctic, north of Norway, which is comparable in size to the New York metropolitan area. Roughly half of it is covered by glacier ice. Yet to this day, the ice volume stored in the many glaciers on Svalbard is not well known. Many attempts have been made to infer a total volume estimate, but results differ substantially. This surprises because of the long research activity in this area. A large record of more than 1 million thickness measurements exists, making Svalbard an ideal study area for the application of a state‐of‐the‐art mapping approach for glacier ice thickness. The mapping approach computes an ice volume that will raise global sea level by more than half an inch if instantaneously melted. If spread over the metropolitan area, New York would be buried beneath a 100‐m ice cover. The asset of this approach is that it provides not only a thickness map for each glacier on the archipelago but also an error map that defines the likely local thickness range. Finally, we provide the first well‐informed estimate of the ice front thickness of all marine‐terminating glaciers that loose icebergs to the ocean. The archipelago‐wide mean ice front cliff is 135 m. Key Points: The presented glacier thickness map for Svalbard is informed by a comprehensive compilation of field measurements Robust numbers for the calving front thickness are key for estimating sea‐level relevant ice discharge Thickness values are complemented by an associated error estimate map